2021
DOI: 10.21037/apm-21-3046
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effect of transcutaneous electrical acupoint stimulation on gastrointestinal function after laparoscopic surgery

Abstract: Background: Postoperative gastrointestinal dysfunction (PGD) leading to nausea, vomiting, and abdominal distension are common complications after laparoscopic surgery for abdominal diseases. However, drugs cannot completely stop PGD. Over the years, transcutaneous electrical acupoint stimulation (TEAS) therapy has shown potential in preventing PGD, but there is no medical evidence that TEAS represents the best choice for the treatment of PGD. This network meta-analysis sought to evaluate the effectiveness of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Therefore, the proportion of abdominal distension in early postoperative period was high, but with the recovery of gastrointestinal function, its ratio will decrease significantly. Previous studies showed that PGISs could increase the risk of postoperative complications, prolong the time of hospitalization, delay the follow-up adjuvant treatment, and reduce the quality of life ( 20 , 21 ). PRO can provide the real feeling of patients after surgery, so that clinicians can carry out the necessary intervention to accelerate postoperative rehabilitation and improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the proportion of abdominal distension in early postoperative period was high, but with the recovery of gastrointestinal function, its ratio will decrease significantly. Previous studies showed that PGISs could increase the risk of postoperative complications, prolong the time of hospitalization, delay the follow-up adjuvant treatment, and reduce the quality of life ( 20 , 21 ). PRO can provide the real feeling of patients after surgery, so that clinicians can carry out the necessary intervention to accelerate postoperative rehabilitation and improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s vital energy and blood lose harmony and are mixed by excess and deficiency syndromes, of which the latter dominates. 34 Therefore, the treatment should try to tonify the kidney to regenerate bone marrow and to replenish vital energy and blood. Activating blood circulation to dissipate blood stasis is fundamental to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional Chinese medicine philosophy, CRF is a kind of “consumptive disease” or “asthenic disease.” The pathogenesis of CRF can be summarized as damaged viscera and constitution caused by a struggle between the vital energy and the pathogenic factor. The patient’s vital energy and blood lose harmony and are mixed by excess and deficiency syndromes, of which the latter dominates 34. Therefore, the treatment should try to tonify the kidney to regenerate bone marrow and to replenish vital energy and blood.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture has been used as an adjunctive therapy in perioperative settings. [4][5][6][7][8][9] Main effects include facilitating analgesia, reducing anesthesia-related complications and organ protection. [6][7][8][9] Acupressure on specific acupoints like Shenmen (HT7) and Ximen (PC4) can significantly reduce stress levels and induces significant relaxation and drowsiness.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Main effects include facilitating analgesia, reducing anesthesia-related complications and organ protection. [6][7][8][9] Acupressure on specific acupoints like Shenmen (HT7) and Ximen (PC4) can significantly reduce stress levels and induces significant relaxation and drowsiness. [10,11] However, whether acupoint stimulation at these specific acupoints could induce sedative effects and reduce propofol consumption in patients undergoing laparoscopic surgery remains unclear.…”
Section: Introductionmentioning
confidence: 99%